(untitled) (Medico Legal Update, 2019)
The purpose of this study was to analyze attentional network test (ANT) and to examine the difference of attention level according to the types of brain dominance between nursing college students and preservice early childhood teachers. The subjects of this study were 79 students in 3rd and 4th grades attending nursing department and early childhood education department of U university. Herrmann’s BDI was used to measure the type of brain dominance and Ant (attentional network test) computer test was performed to measure the level of attention. The data were analyzed by independent t-test to determine differences in brain dominance and attentional level between preliminary nurse and pre-service early childhood teacher and to analyze differences in attention level according to types of brain dominance. The results of this study were as follows: First, there was no significant difference between the two groups in A, B, and C quadrants. In quadrant D, the pre - early childhood teacher’s quadratic thinking score was significantly higher than preliminary nurse quadrant, respectively. Second, there was no significant difference between preliminary nurses and pre – service early childhood teachers in the level of alerting and executive control. At the level of orienting, the preliminary nurse’s orienting score was significantly higher than the pre-service early childhood teacher’s orienting score. Third, alerting effect attention was not significantly different according to the type of brain dominance, but orienting was highest in students in the quadrant A, and executive control was highest in students in quadrant D quadrant burnt.